2013
DOI: 10.3402/ijch.v72i0.19562
|View full text |Cite
|
Sign up to set email alerts
|

Zoonotic infections in Alaska: disease prevalence, potential impact of climate change and recommended actions for earlier disease detection, research, prevention and control

Abstract: Over the last 60 years, Alaska's mean annual temperature has increased by 1.6°C, more than twice the rate of the rest of the United States. As a result, climate change impacts are more pronounced here than in other regions of the United States. Warmer temperatures may allow some infected host animals to survive winters in larger numbers, increase their population and expand their range of habitation thus increasing the opportunity for transmission of infection to humans. Subsistence hunting and gathering activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
60
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 42 publications
0
60
0
2
Order By: Relevance
“…Overall, incidence of CE in people declined significantly in the latter half of the 20th century, which is attributed to the phasing out of sled dogs in Alaska, pathogen reduction in countries of origin for immigrants (e.g., Iceland, New Zealand), the development of cestocidal treatments, and the introduction of control measures in livestock in endemic foci (Katz and Pan, 1958;Loveless et al, 1978;Rausch, 2003). In Alaska, where CE is reportable, 193 cases were reported prior to 1980, but only eight cases were reported after 1990 (Hueffer et al, 2013). A comprehensive review of case reports between 1900 and 1974 identified 123 cases of autochthonous CE in the contiguous United States (Pappaioanou et al, 1977).…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…Overall, incidence of CE in people declined significantly in the latter half of the 20th century, which is attributed to the phasing out of sled dogs in Alaska, pathogen reduction in countries of origin for immigrants (e.g., Iceland, New Zealand), the development of cestocidal treatments, and the introduction of control measures in livestock in endemic foci (Katz and Pan, 1958;Loveless et al, 1978;Rausch, 2003). In Alaska, where CE is reportable, 193 cases were reported prior to 1980, but only eight cases were reported after 1990 (Hueffer et al, 2013). A comprehensive review of case reports between 1900 and 1974 identified 123 cases of autochthonous CE in the contiguous United States (Pappaioanou et al, 1977).…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…Some populations were influenced by climatic changes such as droughts and famines and some other factors such as decreased agricultural lands, increased food-borne diseases, water-borne diseases, vectorborne diseases, and increased death and diseases caused by air pollution also affected humans (3,12,13). Since air pollution significantly influences the human respiratory system, the effect of indoor and outdoor air pollution on the human respiratory system is investigated extensively (11). Generally, diseases that are transmissible from vertebrates to humans are called zoonosis.…”
Section: Introductionmentioning
confidence: 99%
“…The probable role of climate change in human health status, especially in terms of occurrence and severity of diseases, is an extensive field of study, which can be even more complicated and specialized every year (10). Air temperature and air pollution (CO, NO, NO 2 , SO 2 , O 3 ) are of the remarkable human health indicators and higher levels of SO 2 and CO can significantly affect circulatory and skin diseases (11). Till 2008 the residents of some areas of the world were displaced due to sea level rise.…”
Section: Introductionmentioning
confidence: 99%
“…The breadth and topics covered by this research have varied; however, there has been modest focus on health and little is known about disease and health status in polar bears (Fagre et al, unpublished results;Hueffer et al, 2011Hueffer et al, , 2013Letcher et al, 2010;Sonne, 2010;Sonne et al, 2012;Vongraven et al, 2012). Vongraven et al (2012) outlined a circumpolar monitoring framework for polar bears and specifically noted the importance of monitoring population health.…”
Section: Introductionmentioning
confidence: 99%